(untitled) (Analysis in Theory and Applications, 2022)
The more explicit decomposition of the operator and the kernel are utilized to investigate a characterization of the central BMO(R^n)-closure of C_c^∞(R^n) space via the compactness of the commutators of fractional Hardy operator with rough kernel.